Allies & assassins - Somper, Justin. (Little, Brown and Company, 2014)
"Sixteen-year-old Jared inherits the throne of Archenfield after his older brother, Prince Anders, is murdered. He relies on the twelve officers of the court to advise him but soon suspects one of them could be responsible for his brother's death and vows to hunt down the killer, who may be after Jared as well"--